Enhanced thermoelectric properties of Ce-doped Bi2Sr2Co2Oy misfit-layer oxides - Hong, H. Y.; Gwon, S. Y.; Won, S. O.; Park, K. (Elsevier Editora Ltda, 2022)
To improve the thermoelectric properties of Ce-doped Bi2Sr2Co2Oy, the structural and thermoelectric properties of Bi2-xCexSr2Co2Oy (0 < x < 0.15) prepared by both conventional sintering (CS) and spark plasma sintering (SPS) are investigated. As the Ce concentration in the CS processed Bi2-xCexSr2Co2Oy samples increases, the electrical conductivity decreases and the Seebeck coefficient and thermal conductivity increase. On the other hand, the electrical conductivity, Seebeck coefficient, and thermal conductivity of the SPS processed Bi2-xCexSr2Co2Oy samples increase with increasing Ce concentration. The SPS processed samples show a significantly larger dimensionless figure-of-merit ZT compared to the CS processed samples due to the larger electrical conductivity and Seebeck coefficient. The highest dimensionless ZT (0.13) at 973 K is achieved for the SPS processed Bi1.85Ce0.15Sr2Co2Oy. This ZT is nearly three times larger than that of the CS processed Bi2Sr2Co2Oy (0.045) at 973 K. Our results indicate that the SPS and Ce doping are highly effective strategies for improving the thermoelectric properties of Bi2Sr2Co2Oy. (c) 2022 The Author(s). Published by Elsevier B.V. This is an open access article under the CC